2008
DOI: 10.1002/pip.841
|View full text |Cite
|
Sign up to set email alerts
|

Textured silicon surface passivation by high‐rate expanding thermal plasma deposited SiN and thermal SiO2/SiN stacks for crystalline silicon solar cells

Abstract: Expanding thermal plasma (ETP) deposited silicon nitride (SiN) with optical properties suited for the use as antireflection coating (ARC) on silicon solar cells has been used as passivation layer on textured monocrystalline silicon wafers. The surface passivation behavior of these high-rate (>5 nm/s) deposited SiN films has been investigated for single layer passivation schemes and for thermal SiO 2 /SiN stack systems before and after a thermal treatment that is normally used for contact-firing. It is shown th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…This suggests the deposition or annealing conditions of the SiNx were not optimised, since it is possible to attain better passivation with SiNx/Si02 than with Si02 alone [16].…”
Section: Time (Hrs)mentioning
confidence: 99%
“…This suggests the deposition or annealing conditions of the SiNx were not optimised, since it is possible to attain better passivation with SiNx/Si02 than with Si02 alone [16].…”
Section: Time (Hrs)mentioning
confidence: 99%
“…Finally, we note that the lowest J 0E measured on phosphorus-diffused rantex is 8 fA/ cm 2 . 53 The phosphorus diffusion was 140 ⍀ / sq and passivated with an SiO 2 / SiN x stack, where the SiO 2 was 40 nm and grown by a dry thermal oxidation at 1050°C, and the SiN x was 40-70 nm and deposited by chemical vapor using an expanding thermal plasma. The J 0E was ϳ50 fA/ cm 2 after thermal oxidation ͑no hydrogenation͒, ϳ20 fA/ cm 2 after SiN x deposition and 8 fA/ cm 2 after firing for SiN x films of high refractive index.…”
Section: A Photoconductance Measurements On Phosphorusdiffused Siliconmentioning
confidence: 99%
“…The deposition of SiN x on Si wafers can induce stress, thereby affecting the mechanical properties of wafer and potentially impacting the reliability of the finished cell. By measuring wafer bow before and after deposition, multiple authors have found that the stress induced is dependent on the stoichiometry of the SiN x film, with the resulting stress being tensile [210,211] in some cases and compressive in others [212]. Wan et al show an increase in the calculated stress from x = 0.8 to x = 1.2 (where x is the [N]/[Si] ratio in the film after growth) with a peak occurring at ≈1.2, followed by a reduction in stress as x increases beyond this point [212].…”
Section: Induced Mechanical Stressmentioning
confidence: 99%
“…Induced tensile [210,211] or compressive [212] stress caused by SiN x deposition Fourier transform infrared (FTIR) Wafer curvature tests [212] IR polariscopy [40] Raman/µ-Raman spectroscopy [213] Nanoindentation [214] Blistering…”
Section: Crack Formationmentioning
confidence: 99%